Microstructure and mechanical properties of Al2O3/MgAl2O4/ZrO2 eutectic ceramic prepared with induction zone melting. (April 2015) - Zhai, S. Y.; Liu, J. C.; Nie, L. F.; Zhang, Y. B.; Xie, Q. X.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to develop low-cost large eutectic ceramic, Al2O3/MgAl2O4/ZrO2 eutectic ceramic crystal was prepared with induction zone melting. The eutectic phases' composition and microstructure were investigated with X-ray diffraction and scanning electron microscopy, respectively, and mechanical properties were tested with micro-indentation and three-point bending method. The crystal consists of only Al2O3, MgAl2O4 and ZrO2 phases, and no pore is discovered along the whole crystal. The eutectic spacing decreases as the growth rate increases. After a heat treatment in 1550°C for 15 hours in the air, both the crystal weight and the phase size do not change. Its flexure strength reaches up to 720 MPa, which is about four times of that of the sintered ceramic. Its fracture toughness reaches 6·0 MPa m−1/2, more than three times of that of the sintered ceramic.